The Comparative Analysis of Consumer Dispute Resolution in The Karawang Court and Consumer Dispute Resolution Agency (BPSK) - Rahayu, Wulan Sri; Rahmatiar, Yuniar (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
Indonesian Consumer Protection Law which controls the assurance of shoppers affirms in Article 1 passage (1) that shopper security is any exertion that ensures the presence of legitimate certainty to supply security to shoppers. This study method was qualitative and juridical approach. The results showed that the debate determination in court settlement of buyer debate in court or regularly called determination by case. Debate determination exterior the shopper debate determination court as directed in Law Number 8 of 1999 concerning customer assurance can be taken by making a complaint to the BPSK. It can be concluded that the legal certainty of the BPSK decision is the resolution of disputes that are still not in accordance with the expectations of the community. The process in BPSK is often more informal and more confidential than this process in court can make the parties involved feel more comfortable because their privacy is protected.